2000
DOI: 10.1046/j.1463-6395.2000.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure and ultrastructure of the spermatozoa ofTrichogramma pretiosumRiley andTrichogramma atopoviriliaOatman and Platner (Hymenoptera: Trichogrammatidae)

Abstract: Lino‐Neto, J., Báo, S. N. and Dolder, H. 2000. Structure and Ultrastructure of the Spermatozoa of Trichogramma pretiosum Riley and Trichogramma atopovirilia Oatman and Platner (Hymenoptera: Trichogrammatidae). —Acta Zoologica (Stockholm) 81: 205–211 Spermatozoa of the Trichogramma pretiosum and T. atopovirilia are very slender and long, about 0.35 µm in diameter and 283 µm and 106 µm in length, respectively. Under light microscopy, they appear wavy along their entire length. The head contains a small acrosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
77
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 16 publications
(29 reference statements)
7
77
0
3
Order By: Relevance
“…The structure of the H. foveolatum spermatozoa is similar to the general description for insect sperm ( Quicke et al, 1992, Newman and Quicke, 1998, Newman and Quicke, 1999a, Newman and Quicke, 1999b, Newman and Quicke, 2000, Lino-Neto et al, 1999, Lino-Neto et al, 2000a, Lino-Neto et al, 2000b, Lino-Neto and Dolder, 2001a, Lino-Neto and Dolder, 2001b, Lino-Neto and Dolder, 2002, Zama et al, 2001, Zama et al, 2004, Zama et al, 2005a, Zama et al, 2005b, Báo et al, 2004and Fiorillo et al, 2005. They are linear, long and slender as which is observed for the majority of the Hymenoptera.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The structure of the H. foveolatum spermatozoa is similar to the general description for insect sperm ( Quicke et al, 1992, Newman and Quicke, 1998, Newman and Quicke, 1999a, Newman and Quicke, 1999b, Newman and Quicke, 2000, Lino-Neto et al, 1999, Lino-Neto et al, 2000a, Lino-Neto et al, 2000b, Lino-Neto and Dolder, 2001a, Lino-Neto and Dolder, 2001b, Lino-Neto and Dolder, 2002, Zama et al, 2001, Zama et al, 2004, Zama et al, 2005a, Zama et al, 2005b, Báo et al, 2004and Fiorillo et al, 2005. They are linear, long and slender as which is observed for the majority of the Hymenoptera.…”
Section: Discussionsupporting
confidence: 67%
“…Some recent studies have demonstrated that the structure and ultrastructure of spermatozoa in Hymenoptera furnish sufficient variations to provide additional characters for cladistic analysis (Quicke et al, 1992, Dallai and Afzelius, 1995, Lino-Neto et al, 1999, Lino-Neto et al, 2000a, Lino-Neto et al, 2000b, Lino-Neto and Dolder, 2001a, Lino-Neto and Dolder, 2001b, Lino-Neto and Dolder, 2002, Zama et al, 2001, Zama et al, 2004, Zama et al, 2005a, Zama et al, 2005b, Zama et al, 2007, Báo et al, 2004, Araújo et al, 2005and Fiorillo et al, 2005 as has been shown possible in other groups of insects (Baccetti, 1987 andJamieson et al, 1999). The study of spermiogenesis can also provide new characters for improving the accuracy of hypotheses on phylogenetic relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The twisted sperm was considered a characteristic of the parasitic wasps (Wilkes and Lee, 1965, Quicke et al, 1992, Lino-Neto et al, 1999, Lino-Neto et al, 2000aand Lino-Neto and Dolder, 2001b and its occurrence in Symphyta and Aculeata has not yet been reported. Thus, the occurrence of twisted sperm in Microstigmus and in the Crabroninae, Trypoxylon spp.…”
Section: Discussionmentioning
confidence: 99%
“…This nuclear insertion is displaced to one side (asymmetric) as we also observed in Microstigmus. Despite these exceptions, the acrosome in Hymenoptera is made up of an acrosomal vesicle and a perforatorium (bilayered pattern) ( Cruz-Höfling et al, 1970, Wheeler et al, 1990, Quicke et al, 1992, Newman and Quicke, 1999a, Lino-Neto and Dolder, 2001a, Lino-Neto and Dolder, 2002, Zama et al, 2001, Zama et al, 2004, Zama et al, 2005c, Báo et al, 2004, Badke et al, 2005, Fiorillo et al, 2005a, Fiorillo et al, 2005band Mancini et al, 2006 or includes an additional third layer, an extracellular sheath, which covers all the acrosomal vesicle and part of the nucleus ( Quicke et al, 1992, Newman and Quicke, 1998, Newman and Quicke, 1999b, Lino-Neto et al, 1999, Lino-Neto et al, 2000aand Lino-Neto and Dolder, 2001a. As a rule, the perforatorium is dense and compact, but in some bees ( Báo et al, 2004, Fiorillo et al, 2005a and in the Vespidae Agelaia vicina ( Mancini et al, 2006), it appears slightly paracrystalline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation